Elements of the Theory of Computation - Lewis, Harry R.; Papadimitriou, Christos H. (Prentice Hall, 1981)
This text introduces the classical and contemporary theory of computation. Preface, Sets and Relations and Languages, Finite Automata, Context-Free Languages, Turing Machines, Church's Thesis, Uncomputability, Computational Complexity, The Propositional Calculus, The Predicate Calculus, Index.